2021
DOI: 10.1016/j.bar.2020.100959
|View full text |Cite
|
Sign up to set email alerts
|

A conceptual model of accountants' communication inside not-for-profit organisations

Abstract: Accounting communication within organisations can be critical to organisational success, yet aside from formal reports, it has largely been overlooked by accounting researchers. Not-forprofit organisations play a significant societal role and have features that distinguish them from for-profit corporations. This paper aims to further our understanding of accountants' everyday communication in the unique not-for-profit environment, developing a theoretical model of influences on accountants' communication. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
(139 reference statements)
0
6
0
Order By: Relevance
“…He was my doctoral supervisor at the University of South Australia from January 2010 to June 2014. We have published two articles together (Daff and Parker, 2020;Daff and Parker, 2021). The positive experience of my doctoral project no doubt influenced me to highlight Lee's distinguished career and admirable traits (Daff, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…He was my doctoral supervisor at the University of South Australia from January 2010 to June 2014. We have published two articles together (Daff and Parker, 2020;Daff and Parker, 2021). The positive experience of my doctoral project no doubt influenced me to highlight Lee's distinguished career and admirable traits (Daff, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Second, prior research on verbal communication mainly focused on intra-organizational interaction (e.g. Hall, 2010;Daff & Parker, 2021), but this research supplements and complements existing studies by examining verbal communication between banks' management and external accounting users. Third, this research facilitates the recognizing, understanding, and addressing of the hitherto often overlooked and assumed Q&A structure.…”
Section: Introductionmentioning
confidence: 93%
“…Hall (2010), for example, proposed that within organizations managers prefer to interact with accounting through verbal rather than textual communication to deliver meanings, facilitate exchanges of information, ideas, concerns, and promote discussion, while Stone (2011) found small business managers' communication to favor rich verbal communication. Daff and Parker's (2021) recent examination of accountants' communication choice within an organization, however, found that verbal communication varies according to who accountants are communicating with and the topic of concern.…”
Section: Accounting Users and Earning Conferencesmentioning
confidence: 99%
“…Hence, accountability is an alternative to providing legal reports and measures that enhance legitimacy (Cordery and Sinclair 2013;Moxham 2014). Besides, external and internal accounting can support the organizational success once the stakeholders, especially the internal ones, can perceive their roles and outcomes (Daff and Parker 2021).…”
mentioning
confidence: 99%
“…NPOs' characteristics include legal and financial restrictions, depending on donors, findings, or subsidies (Daff and Parker 2021). This dependence on resources can determine organizational survival.…”
mentioning
confidence: 99%